PENGEMBANGAN HANDBOOK STRATEGI PEMBELAJARAN INOVATIF UNTUK MENINGKATKAN KOMPETENSI GURU HOMESCHOOLING DI KOTA BANDUNG [THE DEVELOPMENT OF AN INNOVATIVE LEARNING STRATEGY HANDBOOK TO IMPROVE THE COMPETENCE OF HOMESCHOOLING TEACHERS IN BANDUNG CITY] - Jeremy, Edsel; Winardi, Yonathan (Universitas Pelita Harapan, 2025)
Homeschooling is increasingly popular as an alternative educational model, but it faces challenges, including the need for competent teachers who can cater to diverse student needs. This study aimed to develop and evaluate a competency development program for homeschooling teachers in Bandung City, packaged as a handbook titled